PENGARUH JUMLAH PRODUKSI, HARGA INTERNASIONAL, DAN NILAI TUKAR TERHADAP EKSPOR MINYAK KELAPA SAWIT DI INDONESIA - Nabila, Inda; Marshelly; Yusriyyah, Maudi Zahrany; Tirtana, Dodi (LPPM Universitas Malikussaleh - Indonesia, 2025)
This study aims to analyse the effects of production volume, international prices, and exchange rates on palm oil exports in Indonesia during the period 2012 to 2023. In this study, palm oil exports are the dependent variable, while production volume, international prices, and exchange rates are the independent variables. The data used are secondary data obtained from Statistics Indonesia (BPS) and the World Bank. A quantitative approach is employed, using a multiple linear regression model to analyse time series data. The results of the analysis indicate that, partially, production volume has a negative but insignificant effect on palm oil exports. In contrast, international prices and exchange rates each have a positive and significant impact on the export of this commodity. Simultaneously, the three variables contribute to the changes in Indonesia’s palm oil exports over the 2012–2023 period.